Inhibitory effects of phytoextracts on mycelial growth and conidial germination of the Alternaria brassicae I-6A1y21 isolate causing leaf spot disease in mustard - Kumar, Shailendra; Prasad , S. M.; Kehri, H. K. (Current Botany, 2025)
The study of inhibitory effects of 13 plant extracts such as Lemon, Curry-leaf, Neem, Duranta, Ginger, Garlic, Parthenium, Cinnamon, Asparagus, Zamia, Lantana, Eucalyptus and Datura was taken to observe the effect on mycelial growth and conidial germination of Alternaria brassicae I-6A1y21 isolate. Among these plant extracts, only five plants extracts (Neem, Garlic, Lantana, Eucalyptus and Datura) were used in radial growth and ten plants extracts (Lemon, Curry-leaf, Neem, Duranta, Ginger, Garlic, Parthenium, Cinnamon, Asparagus and Zamia were used against conidial germination. Among the selected plants, the leaf extracts that showed maximum inhibition in mycelial growth was observed with Neem leaf extracts followed by Garlic, Eucalyptus, Datura and Lantana. The chemical Mancozeb fungicide was used at 0.2% level, which caused 100% inhibition in growth of selected isolate I-6A1y21 of A. brassicae. Other plant extracts inhibited the growth of test isolate which varied from 28.24% to 94.97% over control. The radial growth percent inhibition of treatments T3, T5, T4, T1, and T2 was 24.28, 35.45, 51.58, 79.29, and 94.97%, respectively, compared to the radial growth percent inhibition (100%) of treatment with 0.2% mancozeb (test treated, T6). Among the aqueous extracts of ten plants, the aqueous extracts of Azadirachta indica, Zingiber officinale, and Allium sativum were the substances that showed an inhibitory effect on the conidial germination of the A. brassicae I-6A1y21 isolate.